Development of E-modules Based on Mbojo Tribe's Ethnomathematics on the Material of Spatial Buildings on the Learning Outcomes of Class V Students - Fadillah, Uun; Nurul Kemala Dewi; Hikmah Ramadhani Putri (Insights: Journal of Primary Education Research, 2025)
The subpar mathematics learning outcomes of fifth-grade students at SDN Sangiang, particularly in spatial geometry, with the scarcity of contextual and interactive teaching tools to facilitate the learning process. Students require educational resources that connect mathematical principles with local culture to enhance the significance and relevance of learning. Consequently, the creation of an e-module grounded on the ethnomathematics of the Mbojo tribe is crucial for enhancing the quality of education and student performance among fifth-grade pupils at SDN Sangiang. This work aims to Develop an e-module grounded on the ethnomathematics of the Mbojo tribe, utilising spatial geometry. This study employs a Research and Development (R&D) Design utilising a 4-D Development model, comprising the steps of Define, Design, Develop, and Disseminate, to address the learning requirements in the sector. This Design was selected to create a product in the format of a legitimate, practical, and effective e-module. The research findings indicate that the e-module is highly legitimate, achieving 78% from material experts and 96% from media professionals. The e-module's practicality and efficacy were assessed by student and instructor response surveys, along with pretests and posttests. The media practice was commendable, with a student response rate of 91% and a faculty response rate of 94%. The efficacy test yielded an N-Gain score of 0.72, categorising it as high. The findings demonstrate that the e-module grounded on the ethnomathematics of the Mbojo tribe is very viable, practical, and efficacious in enhancing students' mathematics learning outcomes, particularly with spatial figures.